The CGIAR Food Systems Accelerator Cohort 2 Pitch Day Report - Wichenje, Anthony; Nyauncho, Esther; Musau, Caroline; Peterson, Nathania (2024)
The CGIAR Food Systems Accelerator pitch event took place on Thursday, November 14, 2024, at the Protea Hotel, Fire and Ice in Cape Town, South Africa, marking the conclusion of the second cohort’s accelerator program. The event brought together a diverse group of 59 participants, including 11 impact investors, 2 financial institutions, 4 ecosystem enablers, 14 Accelerator Partners, CGIAR scientists, the Ukama Ustawi leadership team, implementation partners (IFDC-2SCALE and The Rallying Cry), and the CGIAR Food Systems Accelerator core team. The Accelerator Partners, representing Kenya, Zimbabwe, Malawi, and Zambia, showcased their businesses through pitches and competed for grant prizes. Sesame for Life Limited from Zimbabwe secured the first prize of $20,000, Nyota Limited from Kenya earned the second prize of $18,000, and Ndkay Zambia Limited received the third prize of $14,000. The remaining seven Accelerator Partners were each awarded $5,000 in recognition of their dedication and efforts throughout the accelerator program. Additionally, four Accelerator Partners from the Agroecology Initiative also had the opportunity to pitch their businesses during the event. However, these businesses did not participate in the competition for grant prizes, as they had already received financial support from the initiative to advance their growth plans.